Classifying Lupus Nephritis: An Ongoing Story - Saba Kiremitci; Arzu Ensari (The Scientific World Journal)
The role of the renal biopsy in lupus nephritis is to provide the diagnosis and to define the parameters of prognostic and therapeutic significance for an effective clinicopathological correlation. Various classification schemas initiated by World Health Organization in 1974 have been proposed until the most recent update by International Society of Nephrology/Renal Pathology Society in 2004. In this paper, we reviewed the new classification system with the associated literature to highlight the benefits and the weak points that emerged so far. The great advantage of the classification emerged to provide a uniform reporting for lupus nephritis all over the world. It has provided more reproducible results from different centers. However, the studies indicated that the presence of glomerular necrotizing lesion was no longer significant to determine the classes of lupus nephritis leading to loss of pathogenetic diversity of the classes. Another weakness of the classification that also emerged in time was the lack of discussions related to the prognostic significance of tubulointerstitial involvement which was not included in the classification. Therefore, the pathogenetic diversity of the classification still needs to be clarified by additional studies, and it needs to be improved by the inclusion of the tubulointerstitial lesions related to prognosis.